Cathode material with core-shell structure comprising buffer layer, preparation method and battery
By introducing a core-shell-buffer layer structure into the cathode material of sodium-ion batteries, the problem of low initial coulombic efficiency of sodium-ion batteries is solved, achieving efficient and safe sodium compensation and improved material performance, making it suitable for mass production.
Patent Information
- Application Number
- CN202511873040.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-12
- Publication Date
- 2026-01-20
AI Technical Summary
Existing sodium-ion battery cathode materials irreversibly consume a large number of sodium ions during the first charge and discharge process due to the formation of an SEI film, resulting in low initial coulombic efficiency and affecting the actual reversible capacity and energy density of the battery. Existing sodium replenishment technologies have safety hazards or are complex and costly.
The cathode material is designed with a core-shell-buffer layer structure. The core is a polyanionic material, the buffer layer is an organic sodium salt, and the outer shell is a sodium ion fast conductor. The buffer layer releases sodium ions during the first charge to compensate for the formation of the SEI film, and the outer shell provides physical protection and ion transport channels.
It achieves an efficient and safe in-situ sodium replenishment process, improves the first coulombic efficiency and energy density, enhances the conductivity and structural stability of the material, extends the battery cycle life, and the process is simple and easy to scale up.
Smart Images

Figure CN121366883A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of sodium ion batteries, in particular to a polyanion type positive electrode material with high initial coulombic efficiency and high energy density, a preparation method thereof and a sodium ion battery comprising the positive electrode material. BACKGROUND
[0002] With the rapid development of new energy vehicle and energy storage market, the demand for low-cost and high-safety battery technology is increasingly urgent. Sodium ion batteries have become one of the ideal choices in the energy storage field due to their abundant sodium resources, low cost and high safety. Among the key materials of sodium ion batteries, the performance of the positive electrode material directly determines the energy density, cycle life and safety performance of the battery.
[0003] Polyanion type positive electrode materials (such as phosphates and sulfates) have broad application prospects in sodium ion batteries due to their stable crystal structure and high working voltage. This type of material has three-dimensional open sodium ion transmission channels, excellent thermal stability and chemical stability, and is considered to be a positive electrode material system with great commercialization potential. However, this type of material generally has the problems of low initial sodium content or limited sodium ion migration channels, which leads to the formation of a solid-state electrolyte interface film (SEI film) during the first charge and discharge process, which irreversibly consumes a large amount of sodium ions from the positive electrode, resulting in low initial coulombic efficiency. This "sodium loss" directly reduces the actual reversible capacity and energy density of the full battery, becoming a bottleneck restricting its commercialization application. Specifically, the initial coulombic efficiency is usually only 80-90%, which means that 10-20% of sodium ions are irreversibly consumed in the first cycle, and this part of capacity loss cannot be recovered, directly affecting the actual available capacity and energy density of the battery.
[0004] To compensate for sodium loss, existing technologies usually use sodium supplement technology, mainly including:
[0005] (1) Positive electrode sodium supplement agent addition: such as introducing Na2C2O4, Na2O2 and other sodium-rich compounds. However, these substances often produce a large amount of gas (such as CO2, O2, etc.) during the sodium removal process, leading to battery swelling and causing serious safety hazards. At the same time, the decomposition products of these sodium supplement agents may have adverse effects on the electrolyte, reducing the overall performance of the battery;
[0006] (2) Negative electrode pre-sodium treatment: such as using metal sodium foil or sodium powder to pre-treat the negative electrode. However, this method is complex and requires strict water and oxygen-free conditions for operation, and active metal sodium is difficult to uniformly treat, posing a huge safety risk and cost problem;
[0007] (3) Design of sodium-rich cathode material: increase the initial sodium content by adjusting the stoichiometric ratio of the material. However, this method often comes at the cost of the working voltage or structural stability of the material, which is not worth the loss. Excess sodium ions may occupy the key ion transport channels, thereby reducing the rate performance of the material.
[0008] Therefore, it is a technical problem to be solved in the field to develop a cathode material structure that can efficiently and safely realize internal sodium supplementation without introducing side effects and improving the overall performance of the material. SUMMARY
[0009] The present application aims to overcome the shortcomings of the prior art and provides a polyanion cathode material with a "core-shell-buffer layer" three-layer structure. This structure introduces a special sodium supplementation buffer layer between the core active material and the outer protective shell, achieving in-situ sodium supplementation without gas and high efficiency during the first charging process, while significantly improving the ion / electron conductivity and structural stability of the material.
[0010] Another object of the present application is to provide a preparation method of the above-mentioned cathode material, which is simple in process, compatible with existing material synthesis routes, and suitable for large-scale production.
[0011] Still another object of the present application is to provide a sodium ion battery comprising the above-mentioned cathode material, which has high initial coulombic efficiency, high energy density and excellent cycle performance.
[0012] To achieve the above-mentioned objects, the present application adopts the following technical solutions:
[0013] In a first aspect, the present application provides a cathode material with a core-shell structure comprising a buffer layer, which comprises, from inside to outside:
[0014] The inner core is composed of a polyanion type sodium ion battery cathode material;
[0015] The buffer layer coated on the surface of the inner core is composed of an organic sodium salt that can electrochemically decompose to release sodium ions during the first charging process without generating gas;
[0016] The outer shell coated on the surface of the buffer layer is composed of a sodium ion fast ion conductor.
[0017] In a preferred embodiment, the general formula of the inner core is Na x M y (XO4)3, wherein M is selected from at least one of Fe, V, Mn and Ti, X is selected from at least one of P, S and Si, x is 3 or 4, and y is 2 or 3; further preferably, the inner core is Na3V2(PO4)3 or Na4Fe3(PO4)2P2O7.
[0018] In a preferred embodiment, the organic sodium salt of the buffer layer is selected from one or more of sodium styrene sulfonate, sodium polyacrylate, sodium citrate, and sodium tartrate.
[0019] In a preferred embodiment, the buffer layer has a thickness of 5-50 nm.
[0020] In a preferred embodiment, the fast ion conductor of the shell is a NASICON-type electrolyte with a general formula of Na3Zr2Si2PO 12 or Na 1+x Zr2Si x P 3-x O 12 wherein 0 < x < 3.
[0021] In a preferred embodiment, the shell has a thickness of 2-20 nm.
[0022] In a second aspect, the present application provides a method for preparing the positive electrode material of any of the above technical solutions, comprising the following steps:
[0023] providing a polyanionic compound core;
[0024] constructing the buffer layer on the surface of the core;
[0025] coating the shell on the surface of the buffer layer.
[0026] In a further embodiment, the step of providing a polyanionic compound core comprises:
[0027] synthesizing Na3V2(PO4)3 or Na4Fe3(PO4)2P2O7 nanoparticles by a hydrothermal method, a sol-gel method, or a high-temperature solid-phase method.
[0028] In a further embodiment, the step of constructing the buffer layer comprises:
[0029] dispersing the core material in a solvent to form a first slurry;
[0030] adding a solution of the organic sodium salt to the first slurry to form a second slurry, the mass ratio of the organic sodium salt to the core material being 1:20 to 1:5;
[0031] evaporating the solvent in the second slurry at 40-80°C and allowing the organic sodium salt to crystallize and adhere to the surface of the core;
[0032] under an inert atmosphere, heat-treating the above-mentioned crystalline substance at 200-350°C to form the buffer layer.
[0033] In a further embodiment, the step of coating the shell comprises:
[0034] The material with the buffer layer is dispersed in a solvent to form a third slurry;
[0035] A zirconium source (such as ZrOCl2·8H2O), a silicon source (such as tetraethyl orthosilicate TEOS), and a phosphorus source (such as NH4H2PO4) are added to the third slurry;
[0036] The shell precursor is attached to the surface of the buffer layer by a liquid phase method to form an attachment, and the attachment powder is obtained by centrifugal separation;
[0037] The attachment powder is sintered at 600-800°C for 2-6 hours under an inert atmosphere to form a crystallized sodium ion fast ionic conductor shell.
[0038] In a third aspect, the present application provides a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode comprises the positive electrode material according to any one of the above technical solutions, or comprises the positive electrode material prepared by any one of the above methods.
[0039] Compared with the prior art, the present application has the following advantages:
[0040] ①Efficient in-situ sodium supplement, improving the initial efficiency and energy density: The organic sodium salt in the buffer layer decomposes at a specific voltage window during the first charging, accurately releasing sodium ions to compensate for the irreversible loss caused by the formation of the SEI film. This process is safe and reliable, and can significantly improve the first coulomb efficiency and energy density of the full battery.
[0041] ②Synergistically improve the conductivity: The amorphous carbon or conductive polymer left after the decomposition of the buffer layer is closely combined with the core and the shell, building an efficient electron conduction network. At the same time, the NASICON shell provides an ultra-fast ion transport channel. The two synergistically improve the rate performance of the material.
[0042] ③Dual protection, enhanced stability: The dense NASICON shell acts as a physical barrier, effectively isolating the electrolyte from the core active material and inhibiting the occurrence of transition metal dissolution and side reactions. The buffer layer relieves the stress between the core and the shell, enhancing the mechanical stability of the overall structure and significantly prolonging the cycle life of the battery.
[0043] ④Process compatible, easy to promote: The preparation method has clear steps and controllable parameters, does not require complex equipment, has good compatibility with existing electrode material production processes, and has the potential for large-scale industrialization.
[0044] Further or more detailed beneficial effects will be described in the specific embodiments in the specific embodiments. BRIEF DESCRIPTION OF DRAWINGS
[0045] Figure 1The figure is a schematic diagram of the structure of the "core-shell-buffer layer" positive electrode material in the specific embodiment. The figure shows a three-layer structure from the inside to the outside: the inner core is a polyanion compound Na3V2(PO4)3, the middle layer is an organic sodium salt buffer layer (thickness 5-50 nm), and the outer layer is a NASICON type fast ion conductor shell layer (thickness 2-20 nm).
[0046] Figure 2 The figure is a comparison chart of the first charge-discharge curves of Comparative Example 1 (pure phase NVP), Comparative Example 2 (NVP@C), Comparative Example 3 (NVP@Na3Zr2Si2PO 12 ), and Example 1 (Na3V2(PO4)3@C@Na3Zr2Si2PO 12 ).
[0047] Figure 3 The figure is a comparison chart of the cycle performance of Comparative Example 1 (pure phase NVP), Comparative Example 2 (NVP@C), Comparative Example 3 (NVP@Na3Zr2Si2PO 12 ), and Example 1 (Na3V2(PO4)3@C@Na3Zr2Si2PO 12 ).
[0048] Figure 4 The figure is an electrochemical impedance spectrum chart of Comparative Example 1 (pure phase NVP), Comparative Example 2 (NVP@C), Comparative Example 3 (NVP@Na3Zr2Si2PO 12 ), and Example 1 (Na3V2(PO4)3@C@Na3Zr2Si2PO 12 ). DETAILED DESCRIPTION
[0049] The present application is further illustrated by the following specific embodiments, but the scope of protection of the present application is not limited thereto. Those skilled in the art can make various modifications and changes to the technical solutions of the present application according to the principles of the present application, and these modifications and changes still belong to the scope of protection of the present application.
[0050] Example 1:
[0051] Core-shell-buffer layer structure Na3V2(PO4)3@C@Na3Zr2Si2PO 12 Preparation of polyanion positive electrode material:
[0052] Synthesis of NVP core: Pure phase Na3V2(PO4)3nanoparticles were synthesized by sol-gel method using ammonium vanadate (NH4VO3), ammonium dihydrogen phosphate (NH4H2PO4) and sodium citrate (Na3C6H5O7) as raw materials. The specific steps are as follows: the stoichiometric ratio of NH4VO3 and NH4H2PO4 was dissolved in deionized water, and citric acid was added as a complexing agent and carbon source. The transparent sol was formed by stirring at 80°C. Then the sol was dried at 120°C for 12 hours to obtain a xerogel, and finally sintered at 750°C for 8 hours under argon atmosphere to obtain pure phase NVP nanoparticles with a particle size of 50-100 nm.
[0053] Construction of buffer layer: 1.0 g of the above NVP core was dispersed in 100 mL of deionized water and ultrasonically treated for 30 minutes to form a uniform slurry. A 0.1 g / mL aqueous solution of sodium styrene sulfonate (NaSS) was prepared, and 1 mL of the solution was slowly added to the NVP slurry while maintaining vigorous stirring. Evaporate in a 60°C water bath for 6 hours to make the organic sodium salt crystallize and uniformly adhere to the surface of the core. The obtained powder was heat treated at 300°C for 2 hours under argon atmosphere to form a buffer layer. The thickness of the buffer layer is about 15 nm.
[0054] Coating Na3Zr2Si2PO 12 Shell: 0.5 g of the above NVP@C intermediate was dispersed in 50 mL of anhydrous ethanol and ultrasonically treated for 20 minutes. 0.28 g of ZrOCl2·8H2O, 0.125 g of tetraethyl orthosilicate (TEOS) and 0.086 g of NH4H2PO4 were added in turn, and the pH was adjusted to 9 with ammonia water. Stir at room temperature for 12 hours to make the precursors hydrolyze and adsorb on the surface of the buffer layer. The precursor powder was separated by centrifugation and washed with ethanol for 3 times, and then dried at 60°C. Finally, the final product Na3V2(PO4)3@C@Na3Zr2Si2PO 12 was obtained by sintering at 750°C for 4 hours under argon atmosphere. The shell thickness is about 10 nm.
[0055] In other embodiments, 2 nm and 20 nm are the process limit end values within the controllable range of the art, and those skilled in the art are aware that they also have corresponding beneficial effects.
[0056] Comparative Example 1:
[0057] A pure phase Na3V2(PO4)3 material without any coating was prepared. Pure phase NVP nanoparticles were prepared by the same sol-gel method as in step 1 of Example 1, as a comparative sample.
[0058] Comparative Example 2:
[0059] Only the composite of NVP core and carbon buffer layer (NVP@C) was prepared, without coating Na3Zr2Si2PO 12 Shell. The same method as in Example 1, step 1 and step 2 was used to prepare NVP@C composite, but without shell coating step.
[0060] Comparative Example 3:
[0061] NVP@Na3Zr2Si2PO 12 Material. The same method as in Example 1, step 1 was used to synthesize NVP core, followed by direct shell coating (skip buffer layer construction step), with other conditions consistent with Example 1, to obtain NVP@Na3Zr2Si2PO 12 composite.
[0062] Performance test:
[0063] The materials obtained in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were used as positive active material, mixed with conductive carbon black and polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1 to prepare slurry, coated on aluminum foil to prepare positive electrode sheet. With metal sodium sheet as the counter electrode, glass fiber as the separator, 1M NaClO4 in EC / PC (1:1 vol%) as the electrolyte, CR2032 type button cell was assembled in an argon glove box. Each group of samples prepared 3 parallel batteries, and the test results were averaged.
[0064] Test results:
[0065] First coulombic efficiency:
[0066] As Figure 2 shown in the figure, the first coulombic efficiency of Comparative Example 1 was only 88.25%, the first coulombic efficiency of Comparative Example 2 was 91.55%, the first coulombic efficiency of Comparative Example 3 was 92.65%, while the first coulombic efficiency of Example 1 was as high as 96.25%, which proved the significant effect of buffer layer sodium supplement. The V 3+ / V 4+ redox platform voltage (about 3.4V vs. Na + / Na) was clearly marked in the figure, and the significant improvement of the material of the application in charge capacity and discharge capacity compared with pure phase NVP.
[0067] Cycle performance:
[0068] As Figure 3The test conditions are 1C rate and 25°C temperature for 500 cycles. The figure shows that the capacity retention of Comparative Example 1 (pure-phase NVP) is 78.3%, the capacity retention of Comparative Example 2 (NVP@C) is 85.2%, the capacity retention of Comparative Example 3 (NVP@Na3Zr2Si2PO 12 ) is 86.7%, and the capacity retention of Example 1 is as high as 92.1%. This fully demonstrates the synergistic effect of the "core-shell-buffer layer" structure in improving the cycle stability of the material, in which the physical protection of the outer shell and the stress relief function of the buffer layer together promote the significant improvement of the structural stability.
[0069] Electrochemical impedance:
[0070] As Figure 4 shown by electrochemical impedance spectroscopy, the charge transfer resistance (Rct) of Example 1 is significantly lower than that of Comparative Examples 1, 2 and 3, confirming the promotion of ion transmission by the NASICON shell.
[0071] Example 2:
[0072] The core-shell-buffer layer structure Na4Fe3(PO4)2P2O7@C@Na3Zr2Si2PO 12 Preparation of polyanion positive electrode material:
[0073] A similar preparation method as in Example 1 is adopted, but the core material is replaced by Na4Fe3(PO4)2P2O7. The specific steps are as follows: FeC2O4·2H2O, NH4H2PO4 and Na2CO3 are used as raw materials, and a high-temperature solid-phase method is used to synthesize Na4Fe3(PO4)2P2O7 nanoparticles.
[0074] Sodium citrate is used as the buffer layer precursor, and the mass ratio to the core material is 1:10, and the buffer layer is formed by heat treatment at 250°C.
[0075] The same Na3Zr2Si2PO 12 coating process as in Example 1 is adopted, and finally Na4Fe3(PO4)2P2O7@C@Na3Zr2Si2PO 12 composite material is obtained.
[0076] The test results show that this material also exhibits excellent electrochemical performance, with a first coulombic efficiency of 95.8% and a capacity retention rate of 90.5% after 500 cycles at 1C rate.
[0077] Example 3:
[0078] Optimization experiment of different buffer layer thickness:
[0079] On the basis of embodiment 1, by adjusting the mass ratio of organic sodium salt and core material, samples with different buffer layer thicknesses are prepared:
[0080] Sample A: mass ratio 1:20, buffer layer thickness about 5nm;
[0081] Sample B: mass ratio 1:12, buffer layer thickness about 15nm;
[0082] Sample C: mass ratio 1:5, buffer layer thickness about 45nm;
[0083] Test results show that the comprehensive performance of sample B is the best, the first coulomb efficiency is 94.5%, and the cycle stability is the best. The sodium supplement effect of sample A is insufficient, but the first coulomb efficiency can still reach 93.0%, and the first coulomb efficiency of sample C can still reach 93.8% due to the influence of ion transmission caused by the too thick buffer layer, which are all better than those of comparative example 1.
[0084] Conclusion:
[0085] The positive electrode material with "core-shell-buffer layer" three-layer structure is successfully prepared, the material ingeniously integrates the sodium supplement function, electronic conductivity enhancement and ion conduction / physical protection into one, and comprehensively improves the electrochemical performance of the sodium ion battery. The experimental results fully prove the effectiveness and advancement of the technical scheme of the present application.
Claims
1. A positive electrode material having a core-shell structure comprising a buffer layer, characterized in that: sequentially from inside to outside comprises: an inner core composed of a polyanionic sodium ion battery positive electrode material; a buffer layer coated on the surface of the inner core, composed of an organic sodium salt capable of electrochemically decomposing to release sodium ions during the first charging process and not generating gas upon decomposition; and an outer shell coated on the surface of the buffer layer, composed of a sodium ion fast ion conductor.
2. The positive electrode material according to claim 1, characterized in that:
3. The positive electrode material according to claim 1, characterized in that: the organic sodium salt of the buffer layer is selected from one or more of sodium styrene sulfonate, sodium polyacrylate, sodium citrate, and sodium tartrate.
4. The positive electrode material according to claim 1 or 3, characterized in that: the thickness of the buffer layer is 5-50 nm. The general formula of the core is Na x M y (XO4)3, wherein M is selected from at least one of Fe, V, Mn, Ti, X is selected from at least one of P, S, Si, x is 3 or 4, and y is 2 or 3.
5. The positive electrode material according to claim 1, characterized in that:
6. The positive electrode material according to claim 1 or 5, characterized in that: the thickness of the outer shell is 2-20 nm.
7. A method for preparing the positive electrode material according to any one of claims 1-6, characterized in that: comprising the following steps: The fast ion conductor of the housing is a NASICON type electrolyte with the general formula Na3Zr2Si2PO 12 or Na 1+x Zr2Si x P 3- x O 12 wherein 0 < x < 3. providing an inner core of a polyanionic compound; constructing the buffer layer on the surface of the inner core; coating the outer shell on the surface of the buffer layer.
8. The method according to claim 7, characterized in that: the step of constructing the buffer layer comprises: dispersing the inner core material in a solvent to form a first slurry; adding a solution of the organic sodium salt to the first slurry to form a second slurry, the mass ratio of the organic sodium salt to the inner core material being 1:20 to 1:5; evaporating the solvent in the second slurry and allowing the organic sodium salt to crystallize and adhere to the surface of the inner core; under an inert atmosphere, heat treating the above crystalline material at 200-350°C to form the buffer layer.
9. The method according to claim 7, characterized in that: the step of coating the outer shell comprises: dispersing the material with the constructed buffer layer in a solvent to form a third slurry; adding a zirconium source, a silicon source, and a phosphorus source to the third slurry; allowing the outer shell precursor to adhere to the surface of the buffer layer to form an adherend by a liquid phase method; under an inert atmosphere, sintering the above adherend at 600-800°C for 2-6 hours to form a crystallized sodium ion fast ion conductor outer shell. The positive electrode comprises the positive electrode material according to any one of claims 1-6, or comprises the positive electrode material prepared by the method according to any one of claims 7-9. 10. A sodium-ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that,